Moral Reconstruction through Routine Activities at the Roudlatul Qur'an Islamic Boarding School, Metro Lampung - Anika Monaziroh; Siti Uswatun Hasanah (TARBAWI : Jurnal Pendidikan Agama Islam, 2021)
The existence and image of Islamic boarding schools are familiar to Muslim communities in Indonesia. Islamic boarding schools are considered capable of forming personalities who have good morals and produce cadres of ulama or da'i. The let's stay on islamic boarding school movement is a pesantren response in the face of modernity, where in this modern era Muslim parents tend to choose Islamic boarding schools as a reference for formal and informal educational institutions, because they expect their children to have the attitudes that have been taught by the Prophet, and the prophets and their friends. This paper describes the cultivation of moral values through routine activities at the Roudlatul Qur'an Islamic boarding school in Metro Lampung. To get the desired results, this research uses qualitative research with a descriptive approach. The results of this study reveal that the pesantren is a gathering place for students to get religious knowledge from a kyai. The process of building morals is obtained from a series of activities ranging from qiyamul lail, congregational prayer, al-quran, diniyyah al-quran and evening study together, as well as manaqib which is held every month on the third week.